Structural health monitoring and seismic response assessment of bridge structures using target-tracking digital image correlation. (15th June 2020) - Ngeljaratan, Luna; Moustafa, Mohamed A.
Highlights: Target-tracking DIC seismic response monitoring from large-scale bridge shake table test. Field monitoring and system identification of pedestrian bridge using target-tracking DIC. 3D DIC displacement measurements are verified against conventional instrumentation. DIC-based system ID is verified for two bridges against results from accelerometers. Abstract: Our nation's infrastructure is aging and deteriorating which increases the need for condition assessment and structural health monitoring. For this purpose, there is a growing interest in using non-contact monitoring methods because of the challenges associated with deploying and installing conventional instrumentation. Target-tracking digital image correlation (DIC) is among these methods and is the focus of this paper. Several research activities have been conducted at the University of Nevada, Reno in the field of dynamic monitoring using DIC and presented here. The first part of the paper is concerned with a large-scale laboratory application where target-tracking DIC was utilized to monitor the response of a bridge structure tested under bidirectional earthquake shaking. The 3D dynamic response of the bridge, along with modal properties, i.e. natural frequency, damping ratio, and mode shapes, were measured or determined using both DIC and conventional instrumentation then compared for validation purposes. The second part of the paper presents results from field monitoring of an actual footbridge under pedestrian loading to determine the vibration frequencies of the bridge, and again compare it against results from conventional accelerometers for validation. From both applications, the DIC is demonstrated to successfully capture (1) peak and residual bridge deck rotation and deformation under different earthquake intensity levels and (2) modal properties for system identification. Practical DIC sampling rates were used to accurately monitor and capture the dynamic response of bridges, which shows a high potential for using DIC for larger structural health monitoring applications and future reconnaissance works.